Unamuno on Life and Immortality (with Nietzsche in the Background) - Matuszewski, Krzysztof (Hybris, 2023)
Unamuno and Nietzsche, two eminent representatives of the philosophy of life, are in disagreement over their attitudes to life and, all the more so, to immortality. Nietzsche takes with both hands from the Greek tradition adding to it his vitalism, built on acknowledging the tragic nature of existence and the ethical obligation of its affirmation. Unamuno is a catholic close to the mysticism of the Spanish baroque and contesting the Thomist unifying vision of Christianity, whose dilatory rationalist pragmatism suppresses the emotional-volitional sphere in man. Nietzsche, whose philosophy is popularly considered to be promoting power and dynamics, the two qualities he discovered in nature and transposed into culture, is accused by him of being effeminate and defeatist. Here is a man exalting life, who devises a weird idea of eternal return, probably as an expression of his longing for duration, instead of using a ready made offer of the Christian vision of immortality. Only such person is a true believer in life and its apologist who wants to perpetuate it into eternity and so, a fortiori, is not afraid to risk it as the transient episode. To be true, Nietzsche was not pusillanimous in this respect: he believed that there are values that are nobler than biological subsistence. Unamuno knows about it but still reproaches him, just like Spinoza, for the Stoic approval of death, filtered through rational evaluations. According to him, vitalism is truly manifested only in the discord for death proclaimed by the will. Reason, which is trying to overpower us with the evidence of the necessity of dying, is the power killing the spirit and getting mired in pusillanimity. By entering the marriage with rationality and approving of the finitude of individual existence Nietzsche has contaminated his declarative accession into vitalism. For Unamuno, vital enthusiasm and enthusiasm for life are convincingly verified through the unconditional faith in personal immortality. In the enunciation from Critique de la Modernité, which can be treated as a pendant to the dispute between Unamuno and Nietzsche, Alain Touraine notes that historically, standpoints that escalate the motives of life and desire, frenetic vitalist doctrines, which promote spontaneity and enthusiasm, have turned out to be lacking empathy and inimical to democracy.